Kepemimpinan Profetik: Telaah Kepemimpinan Pendidikan KH. Ahmad Dahlan dan KH. Hasyim Asy’ari - Syafi’in (Darajat: Jurnal Pendidikan Agama Islam, 2022)
Leadership is interpreted according to each person's perspective. Especially the leadership of Islamic education which so far has received a negative stigma on aspects of education that seem "undemocratic and dictatorial". Such as exemplary crises, effectiveness, awareness and weak performance of leaders. All of these crises are caused by the absence of goals which are the orientation of Islamic education leadership. On that basis Islamic educational leadership must rise by improving its leadership system based on Divine values and the demands of the Prophet Muhammad. Reflecting on this, the researcher offers the concept of Islamic education leadership that is extracted from classical and modern literature. One of them is KH.Ahmad Dahlan and KH. Hasyim Ashari. The key to the development of Islamic world civilization in the days of KH.Ahmad Dahlan and KH. Hasyim Asy'ari showed that he was a key public figure who was very closely related to the success of Muslims in a consistent, dynamic and creative movement and struggle. This study aims to analyze: The values of KH. Ahmad Dahlan in carrying out prophetic leadership, The values of KH. Hasyim Asy'ari in carrying out prophetic leadership. This research is included in library research (Library Research) with the approach used is a qualitative approach. While the results of this study is KH. Ahmad Dahlan in terms of humanism was applied by building a modern Islamic education and preaching from home and while trading. In terms of liberation, KH. Ahmad Dahlan founded the puritan Muhammadiyah organization as a form of social resistance to colonialism. In terms of transcendence, KH. Ahmad Dahlan purifies religion by the practice of rectifying the qibla that is not in accordance with its true direction. And KH. Hasyim Ash'ari in terms of humanism was applied by him by building a traditional Islamic pesantren-based Islamic education. In terms of liberation he ran by establishing the Nahdhatul Ulama organization as a form of movement against the occupation which was oppressing Muslims at that time. In terms of transcendence, it is carried out by means of Sufi attachment and justifies and rejects deviant Islamic orders.